Argentaffin and argyrophil reactions and serotonin content of endocrine tumours. Issue 1 (January 1985) - Wells, C A; Taylor, S M; Cuello, A C
Abstract : Sixty carcinoid tumours were tested in a retrospective study with an immunoperoxidase technique using a monoclonal antibody against serotonin immunoreactive sites, with argyrophil staining using the Grimelius technique, and with argentaffin staining using the Masson-Fontana technique. A good correlation between all three techniques in the diagnosis of ileal carcinoid tumour was found, but the immunoperoxidase technique showed greater sensitivity than the Masson-Fontana technique and greater specificity than the Grimelius technique in the diagnosis of foregut and hindgut carcinoid tumours. The immunoperoxidase technique with a monoclonal antibody against serotonin immunoreactive sites (YC5/45) is recommended as a sensitive and specific test for carcinoid tumours. The reactions in other endocrine tumours are also included.